芎歸香蘇散의 항Allergy 및 항염증 효과 - 권기원(Ki Won Kwon); 신상우(Sang Woo Shin); 박종현(Jong Hyun Park) (동의생리병리학회지, 2008)
The present study was conducted to investigate the anti-allergic activity of Gunggwihyangso-San(GHS). We investigated the anti-allergic effects of GHS in RBL-2H3 basophilic leukemia cells by compound 48/80, a mast cell degranulator and compound 48/80 induced anaphylactic shock in mice. Gunggwihyangso-San significantly inhibited β-hexosaminidase and histamine release from compound 48/80 stimulated RBL-2H3 cells. In addition, GHS effectively inhibited anaphylactic shock in mice by 50% at a dose 80 mg/mouse versus PBS treated control after the I.p injection(8 mg/kg) of compound 48/80. The in vitro anti-inflammatory activities of GHS in LPS-stimulated RAW 264.7 cells were investigated. GHS inhibited NO production in LPS-stimulated RAW 264.7 cells and effectively dowregulated the expression of iNOS mRNA and iNOS protein expression in LPS-stimulated RAW 264.7 cells. These result provide evidences that GHS may be beneficial in the treatment of allergic inflammtory disease. The present study was conducted to investigate the anti-allergic activity of Gunggwihyangso-San(GHS). We investigated the anti-allergic effects of GHS in RBL-2H3 basophilic leukemia cells by compound 48/80, a mast cell degranulator and compound 48/80 induced anaphylactic shock in mice. Gunggwihyangso-San significantly inhibited β-hexosaminidase and histamine release from compound 48/80 stimulated RBL-2H3 cells. In addition, GHS effectively inhibited anaphylactic shock in mice by 50% at a dose 80 mg/mouse versus PBS treated control after the I.p injection(8 mg/kg) of compound 48/80. The in vitro anti-inflammatory activities of GHS in LPS-stimulated RAW 264.7 cells were investigated. GHS inhibited NO production in LPS-stimulated RAW 264.7 cells and effectively dowregulated the expression of iNOS mRNA and iNOS protein expression in LPS-stimulated RAW 264.7 cells. These result provide evidences that GHS may be beneficial in the treatment of allergic inflammtory disease. KCI Citation Count: 1